2020
DOI: 10.1155/2020/3051283
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Drivers’ Intention to Accept Parking App by Structural Equation Model

Abstract: With the concept of sharing economic entering into our lives, many parking Apps are designed for connecting the drivers and vacated parking spaces. However, there are not many drivers who use the mobile Apps to reserve and find available parking spaces, which is largely due to the insufficient information provided by the parking App. In order to better explain, predict, and improve drivers’ acceptance of parking App, the conceptual framework based on technology acceptance model was developed to establish the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…In the theoretical model, the observable variables were not listed in order to simplify the model expression. For higher-order potential variables to be estimated, a factor path of each higher-order potential variable was set to one as the reference index [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the theoretical model, the observable variables were not listed in order to simplify the model expression. For higher-order potential variables to be estimated, a factor path of each higher-order potential variable was set to one as the reference index [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is logical to think that when consumers perceive a quality system it positively affects satisfaction (DeLone & McLean, 2003;Wang, 2008;Justitia, Semiati & Ramadhini, 2019) and therefore the intention to continue using the system, in this case, the application (Li, 2013;Yang et al, 2020).…”
Section: System Qualitymentioning
confidence: 99%
“…In matters of mobile apps, it is not the exception, and it could be said that the quality of the information presented acquires major importance. Having sufficient information guides consumers to make better decisions and allows them to accept and continue using a product or service (Lee & Chung, 2009;Sripalawat et al, 2011;Li, 2013;Justitia, Semiati & Ramadhini, 2019;Yang et al, 2020) more easily.…”
Section: Information Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the government's support and subsidies for the shared parking strategy can effectively promote the implementation of shared parking schemes. Yang et al [16] established a relationship model between drivers' intention to accept a parking app, trust in the parking app, their perceived usefulness of the parking app, and their perceived ease of its use. Cai et al, [17] proposed a parking space allocation method by considering the shared parking strategy, parking price, and parking spaces.…”
Section: Literature Reviewmentioning
confidence: 99%